Numerical Modeling of Sediment Transport in Port of Manado - (NIM : 25514003), NADHILA
Sediment transportation study can be done by numeric modelling, which is by simulating hydrodynamics and sediment transportation models. This numeric modelling uses MIKE 21 FM (Flexible Mesh) Flow Model. The model is calibrated using water level and water current survey data. Hydrodynamics and sediment transportation simulation in the waters around Manado Harbor was done in the duration of one month. Hydrodynamics simulation results show that the current pattern in the Tondano River area is dominated by river debit because in high tide and low tide, the river always flows in the direction of the estuary. In the area in front of the estuary, the current velocity is relatively higher because of the formation of vortex flow caused by the breakwater on the south of the estuary. Results of sediment transportation model sensitivity analysis in respect to the critical shear stress for deposition (τcd) value show that the higher the τcd value, the more sediment precipitation will form, and vice versa. Sediment transportation simulation is done both in the rainy season and in the dry season. Results of the simulation in rainy season show that sediment from the river is carried into the river body and then to the estuary, causing the formation of sediment reaching 0.5 m in the estuary. On the other hand, dry season simulation results show that sediment is centered in the upstream and erosion happens in the estuary. The occurring erosion is not significant, not reaching more than 0.08 m